1990
DOI: 10.1121/1.400110
|View full text |Cite
|
Sign up to set email alerts
|

The loudness of sounds that increase and decrease continuously in level

Abstract: A sound at a low level is heard as much softer after having decreased continuously from higher levels than if presented after a period of silence at that same low level. Canévet [Acustica 61, 256-264 (1986)] demonstrated this phenomenon for a tone that (1) decreased from 65 to 20 dB in 180 s; he also presented a tone that (2) increased from 20 dB, or (3) was presented as pairs of bursts at various levels in random order. Below about 40 dB, loudness changed most rapidly in the decreasing condition so that, at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 2 publications
(2 reference statements)
2
51
1
Order By: Relevance
“…Temporal asymmetries such as found by Stecker and Hafter [44] were also observed for markedly longer stimuli (e.g. [63,64,65,66,67,68]). Fore xample, Susini et al [68] found that sounds with increasing levell ead to greater global loudness judgments than sounds with decreasing levelf or durations between 2a nd 20 s. Theyp roposed "that global impressions resulted from amemory process dominated by the last parts of the sound sequence" [68].…”
Section: Limitations Of the Modelsmentioning
confidence: 55%
“…Temporal asymmetries such as found by Stecker and Hafter [44] were also observed for markedly longer stimuli (e.g. [63,64,65,66,67,68]). Fore xample, Susini et al [68] found that sounds with increasing levell ead to greater global loudness judgments than sounds with decreasing levelf or durations between 2a nd 20 s. Theyp roposed "that global impressions resulted from amemory process dominated by the last parts of the sound sequence" [68].…”
Section: Limitations Of the Modelsmentioning
confidence: 55%
“…The early studies of SIF (e.g., Canévet & Scharf, 1990) included a control condition in which the start and end levels of the downsweep were presented discretely, with an intervening silent period corresponding to the duration of the sweep. The difference between the judgments of the end level with and without a sweep was taken as a measure of SIF.…”
Section: Discussionmentioning
confidence: 99%
“…
A pure tone changing continuously in intensity shows sweep-induced fading (SIF) of loudness as intensity sweeps down and may show a lesser degree of sweep-induced enhancement (SIE) as intensity sweeps up (Canévet & Scharf, 1990); the former effect has been called decruitment, the latter upcruitment. An opposite effect-upsweeps being judged to show more loudness change than downsweeps-has been reported by Neuhoff (1998).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although pairs of such sounds have identical overall spectral contents, durations, levels, and absolute changes in level, many perceptual attributes of the sounds are strikingly different. Ramped and damped sounds differ in timbre (Akeroyd & Patterson, 1995;Irino & Patterson, 1996;Patterson, 1994aPatterson, , 1994b, subjective duration (Schlauch, Ries, & DiGiovanni, 2001), overall loudness (Stecker & Hafter, 2000), and possibly changes in loudness (for durations shorter than ~2 sec, see Neuhoff, 1998Neuhoff, , 2001Seifritz et al, 2002; for longer durations, see Canévet, 1986;Canévet & Scharf, 1990;Canévet, Teghtsoonian, & Teghtsoonian, 2003;Schlauch, 1992;Teghtsoonian, Teghtsoonian, & Canévet, 2000, 2005. The explanation for these effects is not yet clear, with differences in sensory coding providing a possible explanation for brief sounds but not for longer ones.…”
mentioning
confidence: 99%